Aprendiendo a aprender: objetivo clave en el currículum del siglo XXI - Claxton, Guy (CIC. Cuadernos de Información y Comunicación, 2005)
Reflection about changes and challenges which cognitive studies are introducing in present learning models. The new knowledge about how our mind works compel us to consider learning as a great unknown, from which modern psychology is showing now many new aspects.